Adjuvant chemoradiotherapy instead of revision radical resection after local excision for high-risk early rectal cancer. Issue 1 (December 2016) - Jeong, Jae-Uk; Nam, Taek-Keun; Kim, Hyeong-Rok; Shim, Hyun-Jeong; Kim, Yong-Hyub; Yoon, Mee; Song, Ju-Young; Ahn, Sung-Ja; Chung, Woong-Ki
Abstract Background After local excision of early rectal cancer, revision radical resection is recommended for patients with high-risk pathologic stage T1 (pT1) or pT2 cancer, but the revision procedure has high morbidity rates. We evaluated the efficacy of adjuvant concurrent chemoradiotherapy (CCRT) for reducing recurrence after local excision in these patients. Methods Eighty-three patients with high-risk pT1 or pT2 rectal cancer underwent postoperative adjuvant CCRT after local excision. We defined high-risk features as pT1 having tumor size ≤3 cm, and/or resection margin (RM) ≤3 mm, and/or lymphovascular invasion (LVI), and/or non-full thickness excision such as endoscopic mucosal resection (EMR) or endoscopic submucosal dissection (ESD), or unknown records regarding those features, or pT2 cancer. Radiotherapy was administered with a median dose of 50.4 Gy in 1.8 Gy fraction size over 5–7 weeks. Concurrent 5-fluorouracil and leucovorin were administered for 4 days in the first and fifth weeks of radiotherapy. Results The median interval between local excision and radiotherapy was 34 (range, 11–104) days. Fifteen patients (18.1 %) had stage pT2 tumors, 22 (26.5 %) had RM of ≥3 mm, and 21 (25.3 %) had tumors of ≥3 cm in size. Thirteen patients (15.7 %) had LVI. Transanal excision was performed in 58 patients (69.9 %) and 25 patients (30.1 %) underwent EMR or ESD. The median follow-up was 61 months. The 5-year overall survival (OS), locoregional relapse-free survival (LRFS), and disease-free survival (DFS) rates for all patients were 94.9, 91.0, and 89.8 %, respectively. Multivariate analysis did not identify any significant factors for OS or LRFS, but the only significant factor affecting DFS was the pT stage (p  = 0.027). Conclusions In patients with high-risk pT1 rectal cancer, adjuvant CCRT after local excision could be an effective alternative treatment instead of revision radical resection. However, patients with pT2 stage showed inferior DFS compared to pT1.